A new species of Bromus sect. Ceratochloa (Poaceae: Bromeae) from Argentina - Leofanti, Gabriela Agustina; Echeverría, María Lis; Méndez, Alicia López (Phytotaxa, 2024)
A new species of Bromus section Ceratochloa (Poaceae) is described. Bromus alonsae is characterized by its perennial, creeping or semi-creeping habit, blades glaucous green with short and dense pubescence, folded to rolled vernation, and loose and semi-contracted panicles. It begins flowering in October and inhabits the maritime coastal sand dunes of the southeast of Buenos Aires province, Argentina. It differs from B. catharticus var. catharticus in both morphology and phenology.